Measuring territorial cohesion - Medeiros, E. (2019)
The notion of territorial cohesion is still very much misunderstood within EU entities. This is so, despite being mentioned regularly, since 2001, in European Commission Cohesion Reports, and later on being included the Lisbon Treaty, in 2009, alongside the goals of social and economic cohesion. Indeed, over the last couple of decades, few attempts were made to produce a widely accepted methodology which can effectively territorial cohesion trends in a given territory. In this context, this article summarises not only existing proposals to define territorial cohesion, but also some efforts to measure it. It starts by shedding light on the concepts of territory/territorial, and the related analytic dimensions which go beyond the common EU triangle of policy development: economy, society, and environment. In sum, it suggests the inclusion of two additional dimensions, one related toterritorial governance/cooperation, and another associated with spatial planning: polycentricity. Then, it elaborates on the notion of cohesion, and its relation to the territorial dimension of policies, which can be found in several domains/policies: urban, rural, border areas, transports, environment, etc. Moreover, a concrete proposal for a definition of the concept of territorial cohesion is provided in order to make it more comprehensible to political bodies and the scientific community. In this article territorial cohesion is viewed as the process of promoting a more cohesive and balanced territory, (i) by supporting the reduction of socioeconomic territorial imbalances; (ii) by promoting environmental sustainability; (iii) by reinforcing and improving the territorial cooperation/governance processes; and (iv) by reinforcing and establishing a more polycentric urban system. Finally, the article explores the ways in which it is possible to measure territorial cohesion trends. A significant number of statistical indicators are proposed to build an aggregated statistical index (territorial cohesion index) which can measure these trends in a given territory. Here, concrete examples are provided where this proposed methodology was applied: the Iberian (NUTS2) and the Portuguese case (NUTS3) from 1990 to 2010.